2012
DOI: 10.5114/wo.2012.30070
|View full text |Cite
|
Sign up to set email alerts
|

Benign mesocolon schwannoma in PET/CT and immunohistochemistry assessement: a

Abstract: Schwannoma is a common soft tissue tumour, but it appears to be very rare in the gastrointestinal tract. Benign schwannoma develops extremely rarely in the mesocolon, with only 2 patients reported in the literature. A 75-year-old woman was admitted to our Department of Oncological Surgery with an abdominal mass, which was discovered incidentally during abdominal ultrasound examination. Positron emission tomography/ computed tomography imaging with the use of 18F-fluorodeoxyglucose (FDG PET/CT) showed an abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the present report, immunohistochemistry was used because several previous studies have shown the prognostic utility of immunohistochemical markers in several different malignancies and disease conditions [2123]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present report, immunohistochemistry was used because several previous studies have shown the prognostic utility of immunohistochemical markers in several different malignancies and disease conditions [2123]. …”
Section: Introductionmentioning
confidence: 99%
“…Because of the lack of established prognostic markers in TNBCs, in this study we sought to investigate the prognostic significance of adiponectin immunohistochemical expression with respect to disease-free survival (DFS) and overall survival (OS) in a group of homogeneously treated TNBC patients. In the present report, immunohistochemistry was used because several previous studies have shown the prognostic utility of immunohistochemical markers in several different malignancies and disease conditions [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%